SWOT Analysis for Determining Marketing Strategies for Oyster Mushroom Randang in Payakumbuh City - Hendrayani, Eka; Havidz Aima, M. (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2024)
The aim of this study is to explore alternative superior marketing strategies and to make informed decisions for the company by utilizing the SWOT analysis method (Strengths, Weaknesses, Opportunities, Threats) in the Payakumbuh oyster mushroom randang business. The SWOT analysis is conducted using the IFE (Internal Factor Evaluation) matrix, which identifies the company's strengths and weaknesses, and the EFE (External Factor Evaluation) matrix, which highlights the company's opportunities and threats. Additionally, the IE (Internal-External) matrix reveals the company's current position. Data collected is analyzed using SWOT analysis to identify the strengths, weaknesses, opportunities, and threats of the company’s marketing strategy. The study results, as shown by the Cartesian diagram, place the company in Quadrant I, indicating an aggressive stance which is highly advantageous. The company can leverage its strengths to exploit existing opportunities.